Status of Refugees and International Protection Seekers: Administrative-Legal and Socio-Communicative Aspects - Gerasymenko, Yevgen; Zadyraka, Nataliia; Georgiievska, Viktoria; Pohrebniak, Inha; Borets, Andrii (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
The article aims to disclose the administrative, legal, and socio-communicative status of refugees and seekers of international protection. It is demonstrated that refugees' administrative and legal status encompasses the rights and freedoms granted to them, which are classified into two groups. The first group consists of non-specific rights, or fundamental universally recognized rights and freedoms, enjoyed by all non-citizens within the territory of the country of asylum. These include rights realised through general procedures and rights with specific implementation aspects concerning refugees. The second group involves specific rights exclusive to refugees, such as the right to monetary assistance, the right to preferential access to citizenship, and the right to free legal aid during refugee status determination procedures. In addition, it is concluded that the administrative and legal status of refugees also includes specific duties regulated by Ukrainian legislation, such as the obligation to inform the central executive body responsible for refugee policy about travel outside their registered administrative-territorial unit. This study employs a qualitative research method with a literature and legal approach, analyzing primary and secondary legal materials relevant to refugee protection. Through this method, the article offers a comprehensive understanding of the legal frameworks that structure refugee rights and obligations, aiming to strengthen the protection mechanisms for individuals needing international protection.